How coaches` decision-making affect athlete selection: A systematic review and meta-synthesis - Xiang, C.; Zhao, J.; Tengku Kamalden, T. F.; Dong, W.; Luo, H.; Ismail, N. (International Journal of Sports Science & Coaching, 2024)
Athlete selection, as a crucial step for the success of competitive sports, is the last hurdle in the whole sports talent cultivation chain, which is related to the stability and sustainable development of the sports. In athlete selection, coaches play the role of decision-makers in selecting the most suitable athletes for a specific sport or competition from a large pool of talented athletes. Therefore, understanding how coaches` decisions impact athlete selection is crucial in establishing selection rules, formulating effective decision-making, and developing accurate athlete development policies. This review was conducted by searching the Web of Science, PubMed, Scopus, and SPORTDiscus databases for English-language literature on coaching decision-making and talent selection, and screening and categorizing the literature according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A total of 10 articles were included in this review. Based on the meta-synthesis findings, coaches` decision-making styles, intuition, and abilities play a significant role in athlete selection. Additionally, coaches` personalities are also an important factor that influences their decision-making process in identifying and selecting talented players. This review also emphasizes that coach decision-making is essential not only in athlete selection, but also in athlete detection, identification, and development, as coach behavior affects the success of the entire team. In addition, reinforcement of professional competence development and maintenance of continuous learning for coaches is the requirement of the times and the key to the success of athlete selection.